1986
DOI: 10.1042/bj2360023
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-dependence of the relative rate constants for the main geometric and structural photoisomerization of bilirubin IX α bound to human serum albumin. Demonstration of green light at 510 nm as the most effective wavelength in photochemical changes from (ZZ)-bilirubin IX α to (EZ)-cyclobilirubin IX α via (EZ)-bilirubin

Abstract: The kinetics for the quantitatively important reaction: (Formula: see text) that is, the photochemical interconversion between bilirubin and its geometric and structural photoisomers bound to human serum albumin in aqueous solution when various wavelengths of monochromatic light were used, were assayed by h.p.l.c. In order to clarify the wavelength-dependence of the relative rate constants in the individual steps, a light-source with a half-bandwidth of 10 nm was used at increments of 20 nm, in the range from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…In this study, we found that the concentrations of E,Zbilirubin were much lower than those of Z,E-bilirubin, but in contrast to Z,E-bilirubin, it was highest for the group treated McDonagh et al (3,4) propose that E,Z-lumirubin is formed from both Z,Z-and E,Z-bilirubin, whereas Onishi et al (5) propose that E,Z-bilirubin is an obligate intermediate in the formation of E,Z-lumirubin. The serum concentrations of E,E-lumirubin were too low to be identified and quantified with certainty and therefore, are not reported.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In this study, we found that the concentrations of E,Zbilirubin were much lower than those of Z,E-bilirubin, but in contrast to Z,E-bilirubin, it was highest for the group treated McDonagh et al (3,4) propose that E,Z-lumirubin is formed from both Z,Z-and E,Z-bilirubin, whereas Onishi et al (5) propose that E,Z-bilirubin is an obligate intermediate in the formation of E,Z-lumirubin. The serum concentrations of E,E-lumirubin were too low to be identified and quantified with certainty and therefore, are not reported.…”
Section: Discussionmentioning
confidence: 50%
“…However, it was difficult to detect the presence of a small difference of E,Z-lumirubin between the two treatments, due to the low concentrations. In vitro studies have shown, that the formation of lumirubin increases at longer wavelengths of light (3,5,16).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of phototherapy takes place via three possible routes: photo‐oxidation, configurational photoisomerization, and structural photoisomerization. The significance of (EZ)‐C in phototherapy for human neonatal hyperbilirubinemia is as follows: (i) the amounts of (EZ)‐C excreted in bile and urine are greater than the amounts of (ZZ)‐BR reverted from (ZE)‐BR 2 ; (ii) the half‐life of serum (ZE)‐BR is longer than that of serum (EZ)‐C 7 ; (iii) after serum (ZE)‐BR has been excreted in bile, it reverts to (ZZ)‐BR which is absorbed in the intestinal tract, but (EZ)‐C is not observed in the intestinal tract because of the (EZ)‐C polymerization; (iv) enhancement of the efficacy of phototherapy by an increase in the intensity of light energy can not be explained by a mechanism via (ZE)‐BR; and (v) the clinical effect of phototherapy using green light can only be verified by the cyclobilirubin pathway 8 . The clinical effect of phototherapy by the light source in vivo is generally assessed by measurement of serum total BR level.…”
Section: Discussionmentioning
confidence: 99%
“…Onishi et al . and Itoh et al . found that the most efficient wavelength was 500–520 nm in the green region.…”
Section: Mechanism Of Phototherapy For Human Neonatal Hyperbilirubinemiamentioning
confidence: 96%